Layanan Konseling Online Sebagai Upaya Untuk Memfasilitasi Remaja Korban Bullying - Hasanah, Amalia; Ardiansyah, Anas; Aziz, Abdul; Fathan R, Faris; Wardah, Nadya Naqia; Al Batawi, Saiful Bahri; Bahrin, Sitirahma; Alamsyah, Wahyu (Universitas Ibn Khaldun Bogor, 2024)
Bullying is a behaviour that abuses power by hurting someone either physically or emotionally. However, what is very unfortunate and what is more concerning is that there are still many acts of bullying that occur in the school environment. In comparison, schools should be a safe environment for children to play and learn. The level of bullying is most often found at the adolescent level because adolescence is a transitional period when changes occur in the physical, spiritual, or physical, emotional, social, and personal aspects so that changes in adolescent behaviour also occur related to challenges, and what they are facing. The purpose of this research is to facilitate young victims of bullying to safely report the events they experience without any fear of their identity being known. The method used in this paper is literature review which is a systematic, explicit and reproducible method for identifying, evaluating and synthesizing research works and ideas that have been produced by researchers and practitioners. The implementation of guidance and counselling (BK) services is carried out online by utilizing technology as a means to support guidance and counselling. So from the results of this study, we hope to be able to overcome the problems experienced by adolescent (junior high school) victims of bullying that occur in society